PERAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM MENANGANI PANDEMI COVID-19 DI YAMAN - Pratiwi, Anjani; Nashir, Asep Kamaluddin; Kurniawan, Andi (Universitas Prof. Dr. Moestopo (Beragama), 2025)
ABSTRACTYemen is a country with a weak health care system, very vulnerable to exposure to the COVID-19 pandemic. Realizing this, assistance from other parties is needed to overcome these problems. The ICRC as an international non-governmental organization (INGO) has an interest in helping deal with the spread of the COVID-19 virus in Yemen. By using the concepts of human security and non-governmental organizations (NGOs), as well as role theory, this study attempts to analyze the ICRC’s role in dealing with the COVID-19 pandemic in Yemen. Qualitative-descriptive approach is the method used by the author in this study. Based on the research that has been done, several roles were found by the International Committee of the Red Cross during the handling of the COVID-19 pandemic in Yemen. Firstly, as implementer, the ICRC plays a role in mobilizing resources by providing the goods and services needed during the COVID-19 pandemic in Yemen. Second, as a catalyst, the ICRC plays a role in advocating for the wider community through campaign activities and dissemination of information on the prevention of COVID-19. As a partner, the ICRC is working closely with the Authorities in Yemen, as well as the Yemen Red Crescent and other organizations in dealing with the pandemic. The result of this study indicate that in carrying out its role as an international non-governmental organization, the ICRC has not been able to play its fullest role due to obstacles and challenges in dealing with the COVID-19 pandemic in Yemen. Keywords: ICRC, COVID-19, Non-Governmental Organization (NGO), Human Security, Yemen